Geologic Evolution of the Mojave Desert and Southwestern Basin and Range 2002
DOI: 10.1130/0-8137-1195-9.19
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic evolution of the Mojave block of southern California

Abstract: The recorded Cenozoic history of the Mojave Desert region of southern California began in the latest Oligocene, when intense volcanism and tectonism interrupted a long early Tertiary silence. Volcanism commenced across the region in an east-west band ca. 24-22 Ma. Northwest of Barstow, volcanism was accompanied by intense crustal extension and development of a metamorphic core complex. Outside of this relatively restricted area, extension was minor or absent. After extension ceased ca. 18 Ma, volcanism shifted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 82 publications
2
39
0
Order By: Relevance
“…These low anomalies are consistent with the sedimentary deposits indicated by the seismic reflection and borehole studies, which showed that the thickness of the sediments is around 9 km (Kilkenny 1951;Goodman & Malin 1992). The Western Mojave also shows low velocities, likely due to the disruption by the historical extension, strike-slip faulting (Glazner et al 2002) and sedimentary deposits.…”
Section: A P P L I C At I O N T O T H E G a R L O C K Fau Ltsupporting
confidence: 68%
“…These low anomalies are consistent with the sedimentary deposits indicated by the seismic reflection and borehole studies, which showed that the thickness of the sediments is around 9 km (Kilkenny 1951;Goodman & Malin 1992). The Western Mojave also shows low velocities, likely due to the disruption by the historical extension, strike-slip faulting (Glazner et al 2002) and sedimentary deposits.…”
Section: A P P L I C At I O N T O T H E G a R L O C K Fau Ltsupporting
confidence: 68%
“…Cady Fault and Manix/Afton Canyon Fault; Dokka and Travis, 1990). Hills of the Cady Range directly to the south and east of Soldier Mountain are mainly of similar lithology, interspersed with Tertiary volcanic and sedimentary sequences (Glazner et al, 2002). The sand ramp is located on the western side of Soldier Mountain approximately 0.5 km south of the current Mojave River channel which is assumed to be the single main source of aeolian derived material to the sand ramp.…”
Section: Settingmentioning
confidence: 99%
“…Dokka (1989) argued that regional extension occurred within an eastwest-trending belt across most of the Mojave Desert region. In contrast, Glazner et al (2002) suggested that extension was largely confi ned to an ~25-km-wide area centered around the central Mojave metamorphic core complex. Currently there is no strong consensus on the precise timing of extension in the central Mojave Desert.…”
Section: Introductionmentioning
confidence: 88%
“…Early Miocene detachment faulting and extensional basin development generally preceded transformdominated tectonics related to the Pacifi c-North American plate boundary, yet the timing, magnitude, and tectonic signifi cance of these disparate modes of deformation remain controversial (see Glazner et al, 2002, for a review).…”
Section: Introductionmentioning
confidence: 99%